(untitled) (Analysis in Theory and Applications, 2018)
Let L = −∆+V be a Schrödinger operator on R^n(n ≥ 3), where the nonnegative potential V belongs to reverse Hölder class RH_q_1 for q_1 > n2. Let H^p_L (R^n) be the Hardy space associated with L. In this paper, we consider the commutator [b,T_α], which associated with the Riesz transform T_α = V^α(−∆+V)^-α with 0